Русские мальчики: Роман в повестях (продолжение) - Лиханов Альберт Анатольевич (2010)
Экземпляры: аб. (2012) / Инвентарный номер: 54130 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Л 65 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44